The Risk Effect of Primary Dysmenorrhea on Women of Childbearing Age in Ploso Subdistrict of Tambaksari Surabaya - Ulya Rohima Ammar (Jurnal Berkala Epidemiologi, 2016)
Primary dysmenorrhea is menstrual pain without apparent abnormality in the genital device and can be a sign of reproductive system disorders. The prevalence of primary dysmenorrhea is quite high but received less attention from the medical world. This study aims to analyze the risk factors for primary dysmenorrhea in Ploso Village, Tambaksari Sub-District, Surabaya City. This research is an observational analytic study with a cross-sectional design. Sampling is done by multistage cluster sampling. Respondents were 80 women of childbearing age-aged 15-35 years. The results showed that the prevalence of primary dysmenorrhea was 71.3%. Most of the impact of primary dysmenorrhea felt by respondents is a decrease in productivity by 77.2%. Respondents mostly never examined their pain or complaints related to primary dysmenorrhea to doctors or midwives (84.2%) on the grounds the majority of respondents considered the symptoms of primary dysmenorrhea felt to be natural (54.2%). The highest proportion of respondent characteristics was 15-25 years old (51.3%), had a family history (52.5%), had given birth (60%), had menstrual periods of 3-7 days (86%), menarche age 12-13 years (53.8%), had no exercise habits (53.8%), had normal nutritional status (38.8%), and experienced severe stress (25%). The results of the bivariate analysis showed that there was a relationship between age (0,002) and family history with primary dysmenorrhea (p=0,006), and there was no relationship between birth experience, menstrual length, age of menarche, exercise habits, nutritional status, and stress states with primary dysmenorrhea. Women aged 15-25 years old or who have a family history of primary dysmenorrhea are at risk of experiencing primary dysmenorrhea.